Pengontrolan Air Conditioner Cerdas Berdasarkan Jumlah Orang Dalam Ruangan Berbasis Pengolahan Citra - Febriansyah, Aan; Irwan, Irwan; Mushthafa, Eri Nur; Permatasari R, Herda Fitri (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Traditional air conditioning systems often operate without accounting for the number of people in the room, leading to inefficient energy consumption and reduced comfort. This system uses image processing to detect and count individuals within a space, enabling temperature adjustments between 18°C and 28°C and humidity control around 40%-60%. The process begins with video data captured from cameras, which is analyzed using specific algorithms to identify and track the number of occupants. Based on this data, ITRS adjusts temperature and airflow to maintain optimal comfort while minimizing energy usage. Experimental results show that ITRS can control the AC fan speed setting it to low, medium, or high depending on room occupancy and maintain a target temperature range of 20°C to 25°C. By activating air conditioning only when needed and adjusting output based on occupancy levels, the system offers a sustainable and intelligent alternative to conventional HVAC solutions. This responsive approach enhances energy efficiency while providing a comfortable indoor environment.